MITIGASI BENCANA BANJIR TERINTEGRASI PADA MAPEL IPAS SDN LOWOKWARU 2 MALANG - Yuniawatika, Yuniawatika; Fara, Atikah; Ainiyah, Inayatul; Novitri, Qisnah Arsilah; Nurlaili, Titin; Hariyono, Vinny Ermitha Putri (LPPM Universitas Bina Bangsa, 2025)
SDN Lowokwaru 2 Malang, located in Lowokwaru District, is categorized as a medium flood disaster prone area, and students have a low understanding of flood disasters. The low understanding is caused by the lack of educational facilities, socialization programs, and evacuation signs. The target of the socialization includes 27 grade V students, with the aim of understanding and preparedness for flood disasters and mitigation steps. The activity was carried out in six offline meeting sessions from 14 to 19 August 2024, through an interactive method that combines theory and practice. Students learn the causes of flooding, signs that appear before a disaster, the use of disaster-prone maps, and simulate the actions needed during a flood, including steps to reduce its impact. The results of the implementation of the community service socialization are seen from the enthusiasm of students in the socialization which is very high, such as active participation, interest in answering quizzes, and posttest results showing that 85% of students completed, a rapid increase from 22% in the pretest. The integration of flood disaster mitigation in science lessons has succeeded in increasing students' understanding and awareness of disaster preparedness.